Occasional Tillage in a Wheat-Sorghum- Fallow Rotation - A. Schlegel; J. D. Holman (Kansas Agricultural Experiment Station Research Reports, 2017)
Beginning in 2012, research was conducted in Garden City and Tribune, KS, to determine the effect of a single tillage operation every 3 years on grain yields in a wheatsorghum- fallow (WSF) rotation. Grain yields of wheat and grain sorghum were not affected by a single tillage operation every 3 years in a WSF rotation. Grain yield varied greatly by year from 2014 to 2016. Wheat yields ranged across years from mid-20s to 80 bu/a at Tribune and about 10 (hail damage) to near 60 bu/a at Garden City. Grain sorghum yields ranged from less than 60 to greater than 130 bu/a, depending upon year and location. In no year or location were grain yields significantly affected by a single tillage operation. This indicates that if a single tillage operation is needed to control troublesome weeds, grain yields will not be significantly affected.
Keywords: tillage; no-tillage; occasional tillage; wheat-sorghum-fallow rotation